MEDIA A ZJAWISKO AGRESJI W SPORCIE - Białek-Szwed, Olga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The author of the text analyzes how to make selections and create journalistic materials that address the problem of aggression in sport. It draws attention to the attractiveness, but also the dangers of publishing such articles. He wonders about the etiology of the problem, who generates greater demand for aggression: media recipients, broadcasters - journalists, and maybe the heroes themselves - athletes?